2012
DOI: 10.1186/1752-1947-6-57
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of an isolated capitellar fracture of the right elbow in a child: a case report

Abstract: IntroductionAlthough elbow fractures have a high incidence in the pediatric population, fractures of the capitellum are almost exclusively observed in individuals older than 12 years of age. Due to their rarity in children, reports with large numbers of cases are lacking in the literature and the surgical treatment options are poorly defined.Case presentationWe present the case of an 11-year-old Portuguese girl with a displaced fracture of the capitellum of the right elbow, a typical Hahn-Steinthal or Type 1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Furthermore, due to the use of absorbable screws, the second operation is avoided. This conclusion of ours is consistent with the view drawn by Goncalves and others (12). However, there are also reports that the anterior part of the capitellum of a child fracture is thin, and the screw cannot be placed satisfactorily.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, due to the use of absorbable screws, the second operation is avoided. This conclusion of ours is consistent with the view drawn by Goncalves and others (12). However, there are also reports that the anterior part of the capitellum of a child fracture is thin, and the screw cannot be placed satisfactorily.…”
Section: Discussionsupporting
confidence: 93%
“…Previous articles have reported multiple surgical options for children. Some studies have advocated the use of screw or Kirschner wire fixation after open reduction of fracture (11)(12)(13). However, compared with traditional open reduction, arthroscopically assisted surgery in patients has become increasingly popular.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature consists of case reports ( 5 8 , 13 , 16 , 17 , 20 23 , 25 27 , 29 31 , 33 , 38 ), followed by a smaller number of retrospective case series ( 9 , 18 , 19 , 24 , 28 , 32 , 34 37 ). The retrieved literature showed a bimodal distribution of these fractures, with a first peak in childhood (<10 years) ( 7 , 17 , 20 , 31 ) and a second one, the most representative, in pre-adolescents and adolescents ( 5 9 , 13 , 16 , 18 , 19 , 21 25 , 27 30 , 32 38 ). The most frequent associated injury was the ipsilateral elbow dislocation, followed by the involvement of the medial or lateral condyle, or an olecranon or radial head fracture ( 5 , 16 , 17 , 21 , 31 , 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…We carried out a narrative review of the pediatric literature for capitellar shear fractures (shown in Table 1 ). Most of the literature consists of case reports ( 5 8 , 13 , 16 , 17 , 20 23 , 25 27 , 29 31 , 33 , 38 ), followed by a smaller number of retrospective case series ( 9 , 18 , 19 , 24 , 28 , 32 , 34 37 ). The retrieved literature showed a bimodal distribution of these fractures, with a first peak in childhood (<10 years) ( 7 , 17 , 20 , 31 ) and a second one, the most representative, in pre-adolescents and adolescents ( 5 9 , 13 , 16 , 18 , 19 , 21 25 , 27 30 , 32 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fractures of the capitellum constitute an important subtype of TRASH lesions, as delineated by Waters et al 4 These lesions are mostly published in the form of sporadic case reports, but we found 5 patients in this cohort with complications of a TRASH lesion of the elbow. [16][17][18][19][20][21] The true incidence of a missed capitellar fracture as a TRASH lesion is likely higher owing to the nature of the subtle imaging findings, and imaging practices to increase detection have been proposed. 21 Overall, our raters felt that advanced imaging was essential in the diagnosis and proper classification of the capitellar fractures in 84% of patients in this series.…”
Section: Discussionmentioning
confidence: 99%